Penerapan Strategi Komunikasi Pemasaran B2B2C Dalam Penjualan Produk Gerakan Sejuta Siswa Digital (GESSIT) PT. Maleo Edukasi Teknologi (Educourse.Id) - Tri Agusnia Wati; Maharani Ikaningtyas (Politeknik Kampar, 2024)
Communication activities are an important element for companies to influence the level of sales and public awareness about a product offered. Increasing consumer buying interest in a product cannot be separated from good and appropriate communication and promotional activities. With the communication strategy carried out through the implementation of the Business to Business to Consumer (B2B2C) strategy at PT Maleo Edukasi Teknologi (Educourse.id), it helps in increasing sales of the Million Digital Students Movement (GESSIT) products. The aim of this research is to determine the marketing communication strategy carried out by PT Maleo Edukasi Teknologi (Educourse.id) in introducing and increasing sales of the Million Digital Students Movement (GESSIT) products. The research results show that in sales activities for the Million Digital Student Movement products, Educourse.id uses a Business to Business to Consumer (B2B2C) strategy in introducing and increasing sales of the Million Digital Student Movement (GESSIT) products. To build a good image, Educourse.id carries out activities through marketing communications such as holding a free IKM (Independent Curriculum Implementation) socialization event to assist schools in implementing P5 (Pancasila Student Profile Strengthening Project), providing free trial coding days to students. students in various Semarang City schools and also offers profit sharing with the school.